UNSUR-UNSUR KEARIFAN LOKAL MASYARAKAT PESISIR CILACAP (History Department, Semarang State University and Historian Society of Indonesia, 2013)
Local wisdom explains the phenomenon of Watugunung Complex, Sangkuriang Complex, Jaka Sona Complex, and Kamandaka Complex. This phenomenon can be compared to the Oedipus complex phenomena in classical Greek civilization. The similarity phenomenon of Jaka Sona Complex and Oedipus complex is in killing the father. However, Jaka Sona did not marry his mother, even he did not have the desire to his mother while Sangkuriang also killed his father but he failed to marry his mother. Both Watugunung and Oedipus married their mother though Watugunung did not kill his father. Among the five phenomena, only Kamandaka complex is different because he did not kill his father and he did not marry his mother either. He just wanted to marry a woman who looked like his mother’s face. The local wisdoms happened when healing the disease epidemic by using the three-color oil. Keywords: local wisdom, Oedipus Complex, classical Greek civilization, father’s killing, Tigawarna. Kearifan lokal menjelaskan adanya fenomena Watugunung Complex, Sangkuriang Complex, Jaka Sona Complex, dan Kamandaka Complex. Fenomena tersebut dapat dibandingkan dengan fenomena Oedipus Complex dalam peradaban Yunani klasik. Kesamaan fenomena Jaka Sona Complex dengan Oedipus Complex adalah pembunuhan ayah. Namun, Jaka Sona tidak menyunting ibunya, bahkan ia tidak memiliki hasrat. Sangkuriang juga membunuh ayahnya, tetapi gagal mengawini ibunya. Oedipus dan Watugunung sama-sama mengawini ibunya, tetapi Watugunung tidak membunuh ayahnya. Di antara kelima fenomena tersebut, hanya Kamandaka yang paling ringan karena ia tidak membunuh ayahnya dan tidak mengawini ibunya, melainkan ia mempunyai hasrat terhadap wanita yang mirip dengan wajah ibunya. Muncul kearifan dalam bentuk penyembuhan terhadap wabah penyakit dengan minyak tigawarna. Kata kunci: kearifan lokal, Oedipus Complex, peradaban Yunani klasik, pembunuhan ayah, dan Tigawarna.